Evaluating random search strategies in three mammals from distinct feeding guilds. (21st July 2016) - Auger‐Méthé, Marie; Derocher, Andrew E.; DeMars, Craig A.; Plank, Michael J.; Codling, Edward A.; Lewis, Mark A.
Summary: Searching allows animals to find food, mates, shelter and other resources essential for survival and reproduction and is thus among the most important activities performed by animals. Theory predicts that animals will use random search strategies in highly variable and unpredictable environments. Two prominent models have been suggested for animals searching in sparse and heterogeneous environments: (i) the Lévy walk and (ii) the composite correlated random walk (CCRW) and its associated area‐restricted search behaviour. Until recently, it was difficult to differentiate between the movement patterns of these two strategies. Using a new method that assesses whether movement patterns are consistent with these two strategies and two other common random search strategies, we investigated the movement behaviour of three species inhabiting sparse northern environments: woodland caribou ( Rangifer tarandus caribou ), barren‐ground grizzly bear ( Ursus arctos ) and polar bear ( Ursus maritimus ). These three species vary widely in their diets and thus allow us to contrast the movement patterns of animals from different feeding guilds. Our results showed that although more traditional methods would have found evidence for the Lévy walk for some individuals, a comparison of the Lévy walk to CCRWs showed stronger support for the latter. While a CCRW was the best model for most individuals, there was a range of support for its absolute fit. A CCRW was sufficient to explain the movement of nearly half of herbivorous caribou and a quarter of omnivorous grizzly bears, but was insufficient to explain the movement of all carnivorous polar bears. Strong evidence for CCRW movement patterns suggests that many individuals may use a multiphasic movement strategy rather than one‐behaviour strategies such as the Lévy walk. The fact that the best model was insufficient to describe the movement paths of many individuals suggests that some animals living in sparse environments may use strategies that are more complicated than those described by the standard random search models. Thus, our results indicate a need to develop movement models that incorporate factors such as the perceptual and cognitive capacities of animals. Abstract : Searching allows animals to find food and mates. Recently developed methods to distinguish between movement patterns of search strategy models found stronger support for combined correlated random walks than Lévy walks in three species. However, these models were often inadequate, suggesting standard models do not represent search behaviour adequately. (Caribou photo by Craig DeMars. Bear photos by Andrew Derocher)